ENVIRONMENTAL ASPECTS AND PROBLEMS WITH INDIVIDUAL CAR TRANSPORTATION - Nedeliakova, Eva; Kendra, Martin (Doprava a spoje, 2009)
This article deals with environmental impact of the individual car transportation. The increase in the individual car transportation at the expense of the public transportation brings problems in the big cities not only in dynamic, but also in the static transportation.Experience from developed countries show, that regulation of downtown parking and building of car pooling parking lots and their connection to public transportation can solve the problem. The article describes basic intentions of the city parking policy and carpooling services.